A Tolerance‐Enhanced Spontaneous Parametric Downconversion Source of Bright Entangled Photons. Issue 2 (30th December 2022) - Singh, Sandeep; Kumar, Vimlesh; Ghosh, Anirban; Forbes, Andrew; Samanta, G. K.
Abstract: Spontaneous parametric down‐conversion (SPDC), a primary resource of photonic quantum entangled states, strongly depends on the intrinsic phase matching condition. This makes it susceptible to changes in factors such as the pump wavelength, crystal temperature, and crystal axes orientation. Such intolerance to changing environmental factors prohibits deployment of SPDC‐based sources in non‐ideal environments outside controlled laboratories. Here, a novel system architecture based on a hybrid linear and non‐linear solution that is shown to make the source tolerance‐enhanced without sacrificing brightness. This linear solution is a lens‐axicon pair, judiciously placed, which is tested together with two common non‐linear crystals, quasi‐phase‐matched periodically‐poled KTiOPO4, and birefringent‐phase‐matched BiB3 O6 . This approach has the benefit of simultaneous tolerance to the environment and high brightness, which is demonstrated by using the proposed architecture as a stable entangled photon source and a spectral brightness as high as 22.58 ± 0.15 kHz mW −1 with a state fidelity of 0.95 ± 0.02 ± 0.02, yet requiring a crystal temperature stability of only ±0.8 °C, a 5 × enhanced tolerance as compared to the conventional high brightness SPDC configurations is reported. This solution offers a new approach to deployable high‐brightness quantum sources that are robust to their environment, for instance, in satellite‐based quantum applications. Abstract : A novel system architecture based on a hybrid linear and non‐linear solution that allows polarization‐ entangled photon sources with both high brightness and tolerance‐enhanced performance is reported. This solution offers a new approach to deployable high brightness quantum sources robust to their environment, for instance, in satellite‐based quantum applications.